'Today's terrorist is tomorrow's statesman': the United States and Angolan nationalism in the early 1960s - Rodrigues, L. N. (Portuguese Journal of Social Science, 2004)
In the early 1960s, the US government and some private organizations developed close contacts with Angolan nationalist movements. In Washington, this policy gained momentum with the new African policy followed by the Kennedy administration in 1961. Kennedy wanted to extend the ‘new frontier’ to Africa and his administration adopted a policy of favouring self-determination and independence of former colonial territories in that continent. This African policy had several aspects, from the votes and public statements in the United Nations to the increased investment in educational programmes for future African leaders and to the close contacts with those leaders and organizations that could play a decisive role in the future of African nations.